2021
DOI: 10.1093/jamia/ocab284
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of communication workflows between adult day service centers and primary care providers

Abstract: Objectives Our study documented communication workflows across adult day care centers (ADCs) and primary care providers (PCPs) around complex needs of persons living with dementia (PLWD). We also identified barriers and facilitators to productive communication in clinical decision support and clinical information systems. Materials and Methods We conducted 6 focus groups with ADC staff (N = 33) and individual semistructured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…This study’s clinical implications reveal the untapped potential for integrating ADCs into care. Previous research has demonstrated that processes are still siloed within individual ADCs (Dabelko-Schoeny et al, 2020; Zhong et al, 2022), and ADCs are rarely recognized as part of the health care continuum. Centers can help develop care partner toolkits and handbooks to lighten the burden of afterhours caregiving as well as share strategies used by the staff that can be reinforced at home and in other care settings.…”
Section: Discussionmentioning
confidence: 99%
“…This study’s clinical implications reveal the untapped potential for integrating ADCs into care. Previous research has demonstrated that processes are still siloed within individual ADCs (Dabelko-Schoeny et al, 2020; Zhong et al, 2022), and ADCs are rarely recognized as part of the health care continuum. Centers can help develop care partner toolkits and handbooks to lighten the burden of afterhours caregiving as well as share strategies used by the staff that can be reinforced at home and in other care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that ADS staff wanted to exchange information bidirectionally with other care team members. They sought technology that would reduce their reliance on fax and voicemail while enabling them to share serial observations of a person living with dementia's day-to-day health with all members of the care team (eg, ADS staff, health care providers, and caregivers) [7].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Ineffective communication in health care has been associated with costs exceeding US $10 billion, in addition to adverse outcomes and increased mortality [5,6]. We previously found that communication between free-standing community-based ADS centers is hampered by reliance on antiquated methods of information exchange that challenge information sharing and care coordination [7]. When ADS clients experience acute changes in health status or behavior, information is typically reported to primary care providers through fax or voicemail messages, which often results in nonresponse, delayed diagnosis, referral or treatment, and inadequate follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 92% of ADCs lack interoperable electronic health record systems. 5 , 6 Blood pressures outside of normal parameters or acute changes in users’ behavior, for example, are typically reported to primary care providers (PCPs) via facsimile or voicemail message, resulting in a delayed or non-response. This can lead to delayed referrals, diagnoses, and treatment, as well as medication errors and inadequate follow-up that result in negative sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…PCPs and ADC staff mutually agree that effective communication has 4 characteristics: bidirectional, interdisciplinary, succinct, and relevant. 6 To operationalize these components, we developed CareMOBI, ( M health for Organizations to B olster I nterconnectedness) a mobile health (mhealth) application prototype designed to facilitate streamlined communication between ADCs and members of the care team (ie, PCPs and family caregivers) around the health of a mutual patient. A key function of CareMOBI is to synthesize information collected outside of the provider’s office (ie,: in the ADC or at home) and distill the most relevant data points into an exportable clinical summary that can help inform clinical decision making by the PCP.…”
Section: Introductionmentioning
confidence: 99%